2005
DOI: 10.1590/s0102-33062005000400029
|View full text |Cite
|
Sign up to set email alerts
|

Anatomia foliar como subsídio à taxonomia de Hippocrateoideae (Celastraceae) no Sudeste do Brasil

Abstract: A anatomia foliar de treze espécies pertencentes a nove gêneros da subfamília Hippocrateoideae (Celastraceae) foi estudada visando a seleção de caracteres anatômicos para subsidiar a taxonomia dos gêneros e espécies. As espécies estudadas foram: Anthodon decussatum Ruiz & Pav., Cheiloclinium cognatum (Miers) A.C. Sm., Cheiloclinium serratum (Cambess.) A.C. Sm., Cuervea crenulata Mennega, Elachyptera micrantha (Cambess.) A.C. Sm., Hippocratea volubilis L., Peritassa flaviflora A.C. Sm., Peritassa mexiae A.C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 16 publications
1
13
0
4
Order By: Relevance
“…According to Gomes et al (2005), anatomical characters of vegetative organs of Hippocrateoideae species serve as additional subsidies to the external morphology due to the questioning of results with current molecular data, which include Hippocrateaceae within the family Celastraceae (APG 2003). Similarly, other studies were performed with different families, providing contributions for taxonomy and phylogeny (Rio et al 2005, Gomes et al 2009, Hefler & Longhi-Wagner 2010, Mantovani et al 2010.…”
Section: Resultsmentioning
confidence: 99%
“…According to Gomes et al (2005), anatomical characters of vegetative organs of Hippocrateoideae species serve as additional subsidies to the external morphology due to the questioning of results with current molecular data, which include Hippocrateaceae within the family Celastraceae (APG 2003). Similarly, other studies were performed with different families, providing contributions for taxonomy and phylogeny (Rio et al 2005, Gomes et al 2009, Hefler & Longhi-Wagner 2010, Mantovani et al 2010.…”
Section: Resultsmentioning
confidence: 99%
“…Epidermis remnants of the bark situated externally to the suber have diagnostic properties in drugs prepared from those structures because of their high mechanical resistance and their preservation even in crushed and dehydrated material (Farias et al 2009). Ciclocytic stomata, with pyramidshaped subsidiary cells, have been observed on the epidermis of the leaves of various species of Celastraceae (Gomes et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…T. micrantha demonstrates a diffuse disposition of the sclereids and fibers present in the cortical strip, which is preserved in the secondary structures of both stems, different from the continuous arrangement seen in M. ilicifolia (Duarte and Debur 2005). The presence of druses is considered a universal characteristic within the family Celastraceae and therefore has no diagnostic value (Gomes et al 2005), but the observed presence of mono-crystals only in the sobol could aid in distinguishing materials derived from either the underground system or aerial stem (Gomes et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…O tipo, a distribuição e a anatomia dos tricomas e das domácias merecem estudos mais detalhados em Handroanthus e Tabebuia, já que tais estruturas têm sido utilizadas como caracteres com valor taxonômico em membros de Hippocrateoideae, uma das subfamílias de Celastraceae (Gomes et al 2005) e para representantes de Forsteronia, um gênero de Apocynaceae (Rio et al 2005).…”
Section: Discussionunclassified